Pengaruh Penggunaan Kamus Tematik Arab Dalam Meningkatkan Pembelajaran Bahasa Arab - Marwanda, Tengku Sinar; Anwar, Syuhaila; Nasution, Sahkholid (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
ملخص البحث: يهدف هذا البحث إلى تحليل أثر استخدام المعجم الموضوعي العربي في تحسين تعلم اللغة العربية. يتضمن تركيز البحث فعالية القواميس المواضيعية العربية في تحسين إتقان المفردات، وقدرات فهم النص، ومهارات الاتصال، ودافعية التعلم لدى الطلاب. وكان أسلوب البحث المستخدم شبه أو تجريبي، حيث ضم مجموعتين من الطلاب، المجموعة التجريبية التي استخدمت القاموس العربي الموضوعي، والمجموعة الضابطة التي استخدمت طرق التعلم التقليدية. أظهرت نتائج البحث أن استخدام القاموس المواضيعي العربي يزيد بشكل كبير من إتقان الطلاب للمفردات، والقدرة على فهم النصوص، ومهارات الاتصال باللغة العربية. بالإضافة إلى ذلك، أظهر الطلاب الذين استخدموا المعجم المواضيعي العربي دافعية تعلم أعلى مقارنة بطلاب المجموعة الضابطة. وبناء على هذه النتائج، يوصى باستخدام القاموس المواضيعي العربي كوسيلة تعليمية بديلة فعالة لتحسين تعلم اللغة العربية. الكلمات المفتاحية: القاموس العربي المواضيعي، تعلم اللغة العربية، إتقان المفردات. Abstract: This research aims to analyze the influence of using an Arabic thematic dictionary in improving Arabic language learning. The research focus includes the effectiveness of Arabic thematic dictionaries in improving vocabulary mastery, text comprehension abilities, communication skills, and students' learning motivation. The research method used was quasi or experimental involving two groups of students, namely the experimental group which used an Arabic thematic dictionary and the control group which used conventional learning methods. The research results show that the use of an Arabic thematic dictionary significantly increases students' vocabulary mastery, ability to understand texts, and communication skills in Arabic. In addition, students who used the Arabic thematic dictionary showed higher learning motivation compared to students in the control group. Based on these findings, the use of an Arabic thematic dictionary is recommended as an effective alternative learning media to improve Arabic language learning. Keywords: Arabic thematic dictionary, Arabic language learning, vocabulary mastery. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan kamus tematik Arab dalam meningkatkan pembelajaran bahasa Arab. Fokus penelitian mencakup efektivitas kamus tematik Arab dalam meningkatkan penguasaan kosakata, kemampuan pemahaman teks, keterampilan komunikasi, serta motivasi belajar siswa. Metode penelitian yang digunakan adalah kuasi atau eksperimen dengan melibatkan dua kelompok siswa, yaitu kelompok eksperimen yang menggunakan kamus tematik Arab dan kelompok kontrol yang menggunakan metode pembelajaran konvensional. Hasil penelitian menunjukkan bahwa penggunaan kamus tematik Arab secara signifikan meningkatkan penguasaan kosakata siswa, kemampuan memahami teks, dan keterampilan komunikasi dalam bahasa Arab. Selain itu, siswa yang menggunakan kamus tematik Arab menunjukkan motivasi belajar yang lebih tinggi dibandingkan dengan siswa pada kelompok kontrol. Berdasarkan temuan ini, penggunaan kamus tematik Arab direkomendasikan sebagai alternatif media pembelajaran yang efektif untuk meningkatkan pembelajaran bahasa Arab. Kata Kunci: Kamus tematik Arab, Pembelajaran bahasa Arab, Penguasaan kosakata.